A distinct negative leader propagation mode - O. Scholten; B. M. Hare; J. Dwyer; N. Liu; C. Sterpka; I. Kolmašová; O. Santolík; R. Lán; L. Uhlíř; S. Buitink; A. Corstanje; H. Falcke; et al. (Scientific Reports, 2021)
Abstract The common phenomenon of lightning still harbors many secrets such as what are the conditions for lightning initiation and what is driving the discharge to propagate over several tens of kilometers through the atmosphere forming conducting ionized channels called leaders. Since lightning is an electric discharge phenomenon, there are positively and negatively charged leaders. In this work we report on measurements made with the LOFAR radio telescope, an instrument primarily build for radio-astronomy observations. It is observed that a negative leader rather suddenly changes, for a few milliseconds, into a mode where it radiates 100 times more VHF power than typical negative leaders after which it spawns a large number of more typical negative leaders. This mode occurs during the initial stage, soon after initiation, of all lightning flashes we have mapped (about 25). For some flashes this mode occurs also well after initiation and we show one case where it is triggered twice, some 100 ms apart. We postulate that this is indicative of a small (order of 5 km $$^2$$ 2 ) high charge pocket. Lightning thus appears to be initiated exclusively in the vicinity of such a small but dense charge pocket.